333 FRAILTY KNOWLEDGE, USE OF FRAILTY SCREENING TOOLS AND EDUCATIONAL CHALLENGES IN EMERGENCY DEPARTMENTS: A MIXED-METHODS MULTI-SITE ED STAFF SURVEY. (25th October 2022) - Moloney, E; O'Caoimh, R; O'Donovan, MR; Timmons, S; McGrath, K
Abstract: Background: Limited information is available on the extent of Emergency Department (ED) staff knowledge of frailty and frailty screening tools. Educational challenges unique to the ED environment are also little researched. This multi-site staff survey explores frailty knowledge and use of frailty screening tools in Irish emergency departments, as well as detailing educational challenges faced in the ED environment Methods: A mixed-methods multi-site survey of twenty-five Irish adult emergency departments, aimed at all grades of ED staff. An anonymous online survey consisting of twenty-five statements across five categories was distributed via staff email at these sites. Five free-text sections were included after each category. Quantitative data were managed and analysed using IBM SPSS Statistics software. Qualitative results were analysed using reflexive thematic analysis Results: 181 ED staff (nursing, medical and allied health) across all grades responded to the survey. ED nursing staff made up the largest staff category (n=80, 44%). Less than half of respondents had received training on frailty identification (n=88, 48%, p=0.028), yet the majority felt confident of identifying frailty (n=99, 54%, p=0.007). ED staff aged under 35 years felt nursing staff were the most appropriate group to screen for frailty in ED (N=88, 87%, P=0.017). Most respondents felt overwhelmed by time pressures in ED, which left little opportunity for dedicated teaching (n=77, 45%). A thematic map was created to explore obstacles to frailty screening in ED. Conclusion: The opinion of ED staff surveyed was that frailty screening is feasible to undertake in ED but quick, user-friendly frailty screening instruments are lacking. Most ED staff surveyed relied on clinical judgement rather than frailty teaching experience to diagnose frailty syndromes. The provision of inclusive education in ED is challenging. Learning strategies in ED should reflect the demands of the acute care environment and incorporate a flexible, hybrid multi-disciplinary teaching model